ANALISIS PENYAJIAN LAPORAN KEUANGAN, AKSESIBILITAS , SISTEM PENGENDALIAN INTERNAL DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH (Studi Kasus BPKAD KOTA JAMBI) - Manalu, Juni Citra Yohana; Zulfanetti; Nurhayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether the seven components of financial statements have been prepared in accordance with SAP and to analyze the criteria for indicators related to financial statement presentation, accessibility, internal control systems, and accountability in local government financial management at the Jambi City BPKAD. The study employs a documentary and descriptive analysis approach. The results of the study indicate that the financial statements, comprising seven components namely the LRA, LPSAL, Balance Sheet, LO, LAK, LPE, and CaLK have been prepared in accordance with the accrual-based SAP as stipulated in Government Regulation No. 71 of 2010. The results regarding the second objective financial statement presentation, accessibility, and accountability in local government financial management indicate a level of compliance falling within the “Good” category. Meanwhile, the internal control system demonstrates achievement at the “Very Good” category level.